The Design and Operation of Ultra-Sensitive and Tunable Radio-Frequency Interferometers - Cui, Yan (IEEE transactions on microwave theory and techniques, 2014)
Dielectric spectroscopy (DS) is an important technique for scientific and technological investigations in various areas. DS sensitivity and operating frequency ranges are critical for many applications, including lab-on-chip development where sample volumes are small with a wide range of dynamic processes to probe. In this work, we present the design and operation considerations of radio-frequency (RF) interferometers that are based on power-dividers (PDs) and quadrature-hybrids (QHs). Such interferometers are proposed to address the sensitivity and frequency tuning challenges of current DS techniques. Verified algorithms together with mathematical models are presented to quantify material properties from scattering parameters for three common transmission line sensing structures, i.e., coplanar waveguides (CPWs), conductor-backed CPWs, and microstrip lines. A high-sensitivity and stable QH-based interferometer is demonstrated by measuring glucose-water solution at a concentration level that is ten times lower than some recent RF sensors while our sample volume is ~1 nL. Composition analysis of ternary mixture solutions are also demonstrated with a PD-based interferometer. Further work is needed to address issues like system automation, model improvement at high frequencies, and interferometer scaling